THE METAPHYSICAL CONCEPT OF THE DAYAK KANAYATN PEOPLE IN TERMS OF SABAYA DIRI’ BASED ON THE PHILOSOPHY OF GABRIEL MARCEL - Romanus - Piter (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2025)
This study aims to explain the metaphysical concept contained in the term Sabaya Diri’ in the Dayak Kanayatn community in West Kalimantan. Sabaya Diri’ is a human recognition of the existence of others as part of oneself that should not be hurt, hated and belittled. The perspective used in this study is the concept of Metaphysics of Hope from the French philosopher Gabriel Marcel. The method used in this study is a qualitative study method with a literature review. The author collected data on Gabriel Marcel’s thoughts, both physical and digital sources. Meanwhile, the idea of Sabaya Diri’ was elaborated from the author's meaning as a native Dayak Kanayatn. This study found that the term Sabaya Diri’ contains three elements of affirmation of the existence of others as the human self itself. The first, fellow Dayaks are the most solid recognition of Sabaya Diri’ because of the similarity of ethnicity. The second, non-Dayak tribes are Sabaya Diri’ because they are dignified and noble humans. The third, the natural environment is Sabaya Diri’ because of the closeness of the Dayak people's relationality to the universe.